Analisis Penerapan dan Sistem Bagi Hasil Akad Mudharabah Dalam Akuntansi Syariah - Sholihin, Muhammad Rijalus; Mun’im, Abdul (Jurnal Ilmu Manajemen Advantage, 2019)
Islam is the religion that is most widely adhered to by the people of Indonesia, so it is not surprising that since before the year two thousand Islamic banks have emerged in this country, starting from Bank Muamalat which was first in Indonesia and then independent Islamic Banks to various conventional banking systems which opened the. In Islamic banking itself, there are many products offered, ranging from pure savings, financing to Islamic banking services like a conventional one, but there are fundamental principles that distinguish between the two. Therefore there is a need for further understanding of Islamic banking products Through this research, it is expected that the implementation and system of profit sharing in the Mudharabah contract in sharia accounting will be well known and in accordance with Sharia PSAK and the fatwa of the national sharia council (DSN). The results of this study are that the results of the mudharabah contract and sharia accounting are of two types, namely profit loss sharing, and revenue sharing, these two methods can be used in determining profit sharing in carrying out mudharabah contracts.